Efficacy of entomopathogenic nematodes against larvae of Tuta absoluta in the laboratory. Issue 9 (4th January 2016) - Van Damme, Veerle M; Beck, Bert KEG; Berckmoes, Els; Moerkens, Rob; Wittemans, Lieve; De Vis, Raf; Nuyttens, David; Casteels, Hans F; Maes, Martine; Tirry, Luc; De Clercq, Patrick
Abstract: BACKGROUND: Previous studies have indicated the control potential of entomopathogenic nematodes (EPNs) against Tuta absoluta . Here, the potential of Steinernema feltiae, S. carpocapsae and Heterorhabditis bacteriophora is studied when applied against larvae of T. absoluta inside leaf mines in tomato leaf discs by means of an automated spray boom. RESULTS: The studied EPN species were effective against all four larval instars of T. absoluta but caused higher mortality in the later instars (e.g. fourth instar: 77.1–97.4% mortality) than in the first instars (36.8–60.0% mortality). Overall, S. feltiae and S. carpocapsae yielded better results than H. bacteriophora . Steinernema carpocapsae and H. bacteriophora performed better at 25 °C (causing 55.3 and 97.4% mortality respectively) than at 18 °C (causing 12.5 and 34.2% mortality respectively), whereas S. feltiae caused 100% mortality at both temperatures. Under optimal spraying conditions and with the use of Addit and Silwet L‐77 adjuvants, a reduced dosage of 6.8 infective juveniles (IJs) cm −2 yielded equally good control as a recommended dosage of 27.3 IJs cm −2 . CONCLUSION: Under laboratory conditions, S. feltiae and S. carpocapsae showed good potential against the larvae of T. absoluta inside tomato leaf mines. Results need to be confirmed in greenhouse experiments. © 2015 Society of Chemical Industry